442 Thrombocytopenia following transcatheter aortic valve implantation in portico and Evolute recipients. (8th December 2021) - Totaro, Antonio; Sacra, Cosimo; Missiroli, Bindo; Massetti, Massimo; Testa, Gianluca
Abstract: Aims: Thrombocytopenia (TP) following transcatheter aortic valve implantation (TAVI) is a common phenomenon and is associated with mortality and complications. The underlying mechanisms are still unclear. Few data exist on differential risk of thrombocytopenia between different types of transcatheter valves. Methods and results: This retrospective study aimed to evaluate the different behaviour of platelet count in Portico or Evolut recipients. Patients underwent TAVI between Feb 2017 to Aug 2021 at Gemelli Molise Hospital were enrolled and were divided in two groups: Portico ( n = 90) and Evolut recipients ( n = 64). Blood samples and platelets count were collected at admission (T1), implantation day (T2), second post TAVI day (T3), third post TAVI day (T4) and at discharge (T5). Drop platelets count (DPC) was calculated in this way: 100% × (baseline platelet count–nadir platelet count)/(baseline platelet count). CT and echo data were collected. The overall analysis consisted of a total of 154 patients who underwent TAVI. Among these patients, 90 patients (58%) were implanted with Portico valve, and 64 patients (42%) with an Evolut valve. We observed no differences among baseline characteristic between two groups. Interestingly, patients implanted with Portico valve, showed a high degree of thrombocytopenia at time T3, T4 and T5 (respectively, 122 ± 42 vs. 143 ± 43, P 0.004; 111 ± 39 vs. 137 ± 43, P 0.000; 136 ± 56 vs. 173 ± 69, P 0.001). DPC was greater in Portico valve (44 ± 16 vs. 31 ± 15, P = 0.000). No differences were found among inflammation variables (neutrophil lymphocyte ratio, CRP), implantation depth, degree of calcification evaluated with CT (FACTS score) and PVL. Balloon post dilatation (BPD) was performed in 33% of Portico recipients vs. 18% of Evolut recipients ( P 0.044). No correlations were found between DPC and BPD in Portico patients ( r = 0.035, P = 0.744) and Evolut recipients ( r = 0.074, P = 0.569). Conclusions: Our study suggests a more thrombocytopenia in Portico recipients, irrespective inflammation, valve calcification, perivalvular leak, implantation factors. Larger studies are needed to confirm these data.